Development of a rapid molecular method for detection of C. perfringens and other pathogens in water sources - Savahl, Naqsha (Department of Pathology, 2025)
Access to clean water is a basic requirement for all. Global water scarcity necessitates the reclamation and reuse of water. Effective, rapid surveillance for pathogens in recycled water is essential, assisting pathogen detection in water intended for reuse by humans, animals, and industry. Monitoring of repurposed water is essential as it might contain residual microorganisms that are less sensitive to disinfection. Examples are Clostridium perfringens (a spore forming microorganism with a cell envelope that is less sensitive to chemical disinfection and the cause of diarrhoea via contaminated water and food) and Legionella pneumophila (a waterborne, pulmonary pathogen protected from disinfection due to its intracellular lifestyle inside Protists such as Entamoeba). Molecular detection of nucleic acids is a tool enabling more rapid detection of pathogens in water compared to culture-based methods. Molecular tests using nucleic amplification and detection via the polymerase chain reaction (PCR) method needs thermal cycling instruments and thus is limited in resource-poor environments and spaces lacking infrastructure such as electricity. A solution is to use isothermal amplification methods, requiring heated devices at a single temperature and excluding the need for thermal cycling devices. A battery-operated heated device suffices for isothermal methods such as Recombinase Polymerase Amplification (RPA) and requires less time compared to PCR. Furthermore, isothermal amplification, when combined with the detection of generated amplicons on lateral flow devices, excludes the need for detection methods requiring electrified equipment. The study described here aimed to evaluate RPA, combined with lateral flow detection of labelled amplicons, as a tool to detect deoxyribonucleic acid (DNA) from two waterborne pathogens, i.e., Clostridium perfringens (C. perfringens) and Legionella pneumophila (L.pneumophila). In-house designed primers targeting the C. perfringens phospholipase C gene (plc) and previously published primers to detect L. pneumophila mipA gene were evaluated using conventional PCR and RPA. The lowest amount of DNA needed for amplification and detection was determined using PCR and both agarose gel electrophoreses and lateral flow detection (LFD). For LFD, labelled primers were used to generate dual-labelled amplicons that were captured and detected on a commercial lateral flow device. The RPA-LFD method was then tested with DNA extracted from a limited number of water samples provided by the local municipality. Lastly, as efficient DNA extraction is a limiting step in molecular detection. Consequently, three commercial, manual DNA purification methods were evaluated for their ability to extract DNA from C. perfringens. The generated data showed successful detection of DNA from both pathogens via RPA-LFD). A minimum of at least 1x10-3 ng of pure DNA, extracted from the cultured pathogens, were efficiently amplified, and detected for both microorganisms. Future work should evaluate the method more extensively with DNA extracted from variety of real-world water samples as PCR inhibitors in water from different resources might influence the sensitivity of the method. Regarding DNA extractions, we compared three different DNA extraction and purification methods (solid phase, desalting and magnetic bead purification) to obtain fit for purpose DNA from cultured C. perfringens. Extraction kits were also compared for equipment and infrastructure needed, efficiency of extraction, cost, and ease of use. All kits generated DNA fit for downstream amplification, but consideration should be given to kits that require fewer steps to obtain pure DNA and use minimal equipment. Kits with a removal step for PCR inhibitors in water should also preferentially be used. In conclusion, the data shows that RPA-LFD could be a feasible method to monitor pathogens in water. Further development of the RPA-LFD method using dual labelled amplicons are necessary, including validation of the method with an expanded set of real-world water samples. The method should further be combined with viability testing, to confirm that DNA detected from samples originates from viable microorganisms and not cell free DNA present in water.